2013
DOI: 10.1097/ccm.0b013e318298ad3a
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin Attenuates Vascular Leakage via Inhibiting Neutrophil Activation in Acute Lung Injury

Abstract: Objective To test the hypothesis that restoration of antithrombin plasma concentrations attenuates vascular leakage by inhibiting neutrophil activation through syndecan-4 receptor inhibition in an established ovine model of acute lung injury. Design Randomized controlled laboratory experiment. Setting University animal research facility. Subjects Eighteen chronically instrumented sheep. Interventions Following combined burn and smoke inhalation injury (40% of total body surface area, third-degree flame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 35 publications
(46 reference statements)
3
43
0
1
Order By: Relevance
“…Details regarding article selection are presented in Figure 1. Compared to our previous review published in 2012, the updated search found six additional articles reporting on preclinical studies (36,37,(42)(43)(44)(45), and eight new articles reporting on human trials of nebulized anticoagulants (50,51,(53)(54)(55)(56)60,61).…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details regarding article selection are presented in Figure 1. Compared to our previous review published in 2012, the updated search found six additional articles reporting on preclinical studies (36,37,(42)(43)(44)(45), and eight new articles reporting on human trials of nebulized anticoagulants (50,51,(53)(54)(55)(56)60,61).…”
Section: Search Resultsmentioning
confidence: 99%
“…The reasons for not finding an inhibitory effect on inflammation in all studies remain unexplained. Interestingly, one animal study combining nebulized heparin with AT found antiinflammatory effects, while 'triple therapy' by adding TPA abolished the inhibitory effect on inflammation (42). Hence, anticoagulants may induce anti-inflammatory effects due to pathways crosslinking coagulation and inflammation in models of lung injury; however, combination of various anticoagulants and dosages are of importance in influencing these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations